Integração da vigilância em saúde e da atenção primária à saúde no Brasil: uma revisão de escopo - Queiroz, Adriana Lúcia Silva de (2023)
The Unified Health System (UHS) aims to guarantee the population full access to health services at all levels of care. However, for UHS to achieve its purpose of being a unified, integrated and universal health system, some challenges still need to be overcome. Among these , the low insertion of Health Surveillance (HS) actions stands out in Primary Health Care (PHC). PHC is considered the gateway for users to the Brazilian health system, and proximity to the population helps Family Health (eSF) teams to become aware of the health situation in their area of operation, allowing for the identification of problems and its determinants in loco , which expands the ability to intervene in the population's health problems. HS it consists in one set of 04 areas that complement each other, namely: Environmental Health Surveillance (EHS), Occupational Health Surveillance (OHS), Epidemiological Surveillance (ES) and Sanitary Surveillance (SS), and how PHC also aims to provide integral to health. For the integration of PHC and HS to happen, it is necessary to assess which Skills about HS are in the domain of professionals of PHC and which are still incipient, so that managers and health professionals have a starting point. This study constitutes the first stage of the research Elaboration and validation of a competency matrix in Health Surveillance for Primary Care professionals and aims to carry out a scope review, to identify the literature on the integration of PHC and HS in Brazil and systematically describe what actions are being proposed or carried out. Initially the scoping review protocol was published in the Open Science Framework. The Joanna Briggs Institute and PRISMA-ScR methodology was used for scoping reviews. Publications with a quantitative, qualitative or mixed approach, published in English, Spanish or Portuguese, in indexed sources or in the “gray literature”, available in online format, were included. Search strategies were carried out in eight bibliographic databases, in the Brazilian digital library of theses and dissertations, in the official journal, google and google academic and even used the snowball technique. 12,933 publications were identified and analyzed, and 134 publications were included in the qualitative synthesis. The reviewed sources of evidence were divided into four categories: (i) HS actions and professionals involved; (ii) Health Education and Public Health Professional; (iii) Planning and management and (iv) Health Indicators. Five actions for the HS and PHC integration process were recommended: (i) institutional rearrangement of health services for shared management of HS and PHC; (ii) social participation in the decisions of the integrated territory; (iii) presence of HS nuclei in the Primary Health Care Units, made up of HS or PHC professionals; (iv) constant dialogue between the areas, including permanent education in health; and (v) shared monitoring of indicators between HS and PHC, with permanent evaluation. Considering the decentralization of the Brazilian health system, with these recommendations, it is expected that municipal health services will play a leading role in order for the integration of HS and PHC to take place in Brazil.